PENGARUH LITERASI DIGITAL DAN SOFT SKILL TERHADAP KESIAPAN KERJA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS SEBELAS MARET SURAKARTA - Dian Muliasari; Sudarno; Dini Octoria (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to determine the influence of digital literacy and soft skills on the work readiness of Economics Education students. This research is a quantitative descriptive research with a population of 177 students. The sampling technique used in this research was proportionate random sampling which resulted in a sample of 130 student respondents. Data collection is carried out through questionnaires or questionnaires which are distributed via a google form link. The data analysis used is multiple linear regression analysis with SPSS. The results shown from this research are: First, digital literacy has a positive effect on the work readiness of UNS Economics Education Students. Second, soft skills have a positive effect on the work readiness of UNS Economics Education Students. Third, digital literacy and soft skills simultaneously have a positive effect on the work readiness of UNS Economics Education Students. Key words: digital literacy, soft skills, work readiness